Effect of once‐daily insulin detemir on oral antidiabetic drug (OAD) use in patients with type 2 diabetes. (13th December 2013) - Vora, J.; Caputo, S.; Damci, T.; Orozco‐Beltran, D.; Pan, C.; Svendsen, A. L.; Sølje, K. S.; Khunti, K.
Summary What is known and objective There are acknowledged benefits to continuing metformin when initiating insulin, but there appears to be growing concern over the role of sulphonylureas and thiazolidinediones when used in combination with insulin. This analysis investigates the effects of continuing or discontinuing oral antidiabetic drugs (OADs) following the initiation of once‐daily insulin detemir. Methods SOLVE is a 24‐week, multinational observational study of insulin detemir initiation in patients with type 2 diabetes mellitus treated with one or more OADs. Results In the total cohort (n = 17 374), there were significant improvements in HbA1c (−1·3%, 95% CI −1·34; −1·27%) and weight (−0·6 kg, 95% CI −0·65; −0·47 kg), with an increase in the incidence rate of minor hypoglycaemia (+0·256 events ppy, P < 0·001), but not severe hypoglycaemia (−0·038 events ppy, P < 0·001). Study participants had information on OAD use either prior to (n = 17 086) or during insulin initiation (n = 16 346). HbA1c reductions were significantly greater in patients continuing treatment with metformin (−1·3% vs. −1·1%, P < 0·01), thiazolidinediones (−1·3% vs. −1·0%, P < 0·01) and DPP‐IV inhibitors (−1·3% vs. −0·9%, P < 0·001). Final insulin doses were significantly greater in patients discontinuing treatment with sulphonylureas (0·29 vs. 0·26 IU/kg, P < 0·001), glinides (0·28 vs. 0·26 IU/kg, P < 0·01), thiazolidinediones (0·31 vs. 0·26 IU/kg, P < 0·001) and DPP‐IV inhibitors (0·35 vs. 0·29 IU/kg, P < 0·001) compared with patients continuing these respective agents. All patient subgroups had a mean weight loss irrespective of OAD continuation, apart from those continuing thiazolidinediones (+0·2 kg). The largest improvements in weight were seen following the withdrawal of sulphonylureas and thiazolidinediones (−1·1 and −1·1 kg, respectively). What is new and conclusion Discontinuation (or switching) of OADs at the time of insulin initiation appears to be governed principally by concerns about hypoglycaemia and weight. HbA1c improvements were smaller in patients discontinuing OADs at the time of insulin initiation and may be associated with insufficient insulin titration.